PEMBUATAN APLIKASI E-COMMERCE CUSTOMIZE PAKAIAN DAN PREDIKSI STOK DENGAN MENGGUNAKAN METODE REGRESI LINEAR SEDERHANA - Febryan Valentino Tansen; Bagus Mulyawan; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
Bigoneshop is an online store that sells various types of clothing. In this era, there is a lot of interest from buyers who want to buy clothes by designing it themselves. Therefore, a new innovation will be made from the world of clothing, website that sells various kinds of clothing and will apply editing or design features directly to the Bigoneshop website and can request new clothes. So, it will provide flexibility for buyers to design their clothes and make it easier for buyers when making transactions. Editing features and requests clothes are using HTML 7 with the fabric.js and canvas libraries. In addition to the above features, a feature will be made to predict the stock that is intended for the admin Bigoneshop website. With this feature, it is expected to reduce errors in the process of providing goods. In this feature you will use the Simple Linear Regression method to make the prediction process. From the results of the tests conducted, it was found that with custom clothing websites and stock prediction features, it can make it easier for buyers to customize clothing online and very helpful for admin in predicting stock.